The Effect of Profit Sharing Ratio, Zakat Performance Ratio and Islamic Performance Ratio on Profitability with Financing to Deposite Ratio (FDR) as a Moderating Variable in Islamic Commercial Banks 2017-2023 - Putri, Francinita; Santoso, Suryo Budi; Pramono, Hadi (PT FORMOSA CENDEKIA GLOBAL, 2025)
In practice, the performance measurement of Islamic banks has only presented the performance of Islamic finance in a materialistic aspect, without revealing spiritual and social values. In fact, it is very important to measure the performance of Islamic finance to realize stakeholder trust. Therefore, this study was conducted to find out whether Islamic banks in Indonesia have been able to realize stakeholder trust. This study is a quantitative study with the population of Islamic Banking companies for the 2017-2023 period found in the OJK. The sample selection in this study used purposive sampling. The analysis method uses a panel data regression model using the E-views software 12. The results show that the zakat performance ratio and the zakat performance ratio with FDR moderation show an influence on profitability. Meanwhile, the profit sharing ratio and the Islamic performance ratio with FDR moderation have no influence on profitability.